(3QSGdI aj OaY THgI cd cdGe cGPHs - (3LdGd GdOjf eMeO Hf CSYO GdUOjbj GdOhGfj, GdOhGfj,J (B918 (3g` s
(3ChdgG (B:s
(3CeG HYO MeOkG ddg efGM eaGJjM GdeYVdGJ aJGM eZGdjb GdeTcdGJ aCbhd aCNhGfi ef WdGH Gdjbjf gPg fgGjI GdcdGe ai Md GdeZGdWI s
(3BNQgG (B:s
(3hGdfSGA dGJNJda ai YOe chfgG UGObg Gh cGPHI hHPdc Je s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GfXQg eY GdeNWhW Qbe (B259s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B32s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs